Effects of distance from forest edge on upper storey birds in Ayer Hitam Forest Reserve, Malaysia - Rosli, Zamri (2012)
Tropical rainforest has lost much of its natural biodiversity due to deforestation. This activity leads to the creation of numerous forest patches and thus causes edge effects. Although several studies have examined the effects of edges on bird populations, little is known about effects of the forest edge on the upper storey birds in the isolated forest especially in tropical rainforest. Thus, a study was conducted in the isolated Ayer Hitam Forest Reserve (AHFR), Puchong, Selangor to; (i) examine the species composition, abundance, density and diversity of the upper storey birds at different distances from forest edge, (ii) detect any correlations in the upperstorey birds with microhabitats and microclimates factors, (iii) to identify which group and species of the upper storey bird that was affected by the edge effects and iv) to determine which micro-environmental factors have strong effects on the upper storey birds.